Introducing Dart Sass a practical introduction to the replacement for Sass, built on Dart - Libby, Alex (Apress, 2019)
Leverage the power of Dart Sass to quickly create valid CSS styles for use within websites. This short project-oriented book simplifies the process of creating and manipulating Sass code in the browser, for websites, or online applications, using little more than a text editor or free software. Designed to be much faster and simpler to use, yet still maintain the same features as past versions of Sass, Dart Sass offers a host of benefits of using it against writing CSS manually. You will be equipped with a starting toolset that you can use to develop future projects, incorporate into your existing workflow and reduce any dependency on graphics applications such as Illustrator for simple projects. Dart Sass is a complete rewrite of what many know as Ruby Sass but you don't have to convert your whole work process immediately to working with Sass. You will learn how to incorporate as little or as much as you need, and how to build on it as your skills develop. We live in an age where speed and simplicity are of the essence - Introducing Dart Sass provides a perfect way to create valid CSS quickly, efficiently, and with the minimum of fuss.